2015
DOI: 10.5137/1019-5149.jtn.14594-15.0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemical and motor function analysis of alpha lipoic acid and n-acetyl cysteine treatment on rats with experimental spinal cord injury

Abstract: SCI develops in two phases: primary and secondary injury. The mechanical impact of the trauma destroys neurons and disrupts the architecture of the tissue, composing the primary phase, but it also induces the overproduction of deleterious substances, which provokes the secondary injury cascade (13).For the secondary injury cascade, numerous distinct mechanisms have been hypothesized and analyzed. The activation of microglia and oxidative stress are the pivotal secondary injury mechanisms after traumatic injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There is strong evidences that show PON1 has beneficial effect against atherosclerosis by protection of HDL-C from peroxidation and plasma membrane from injury thereof. In clinical studies on patients with type 1 diabetes have demonstrated the reduced level of PON1 activity compared to healthy group (15). Different studies have shown that antioxidant therapy is one of the most important treatment strategies for diabetic patients (18).…”
Section: Effect Of Alpha Lipoic Acid On Serum Level Of Pon1 Activity and Correlation Between Pon 1 Activity With Hdl-c And Atherogenic Inmentioning
confidence: 99%
“…There is strong evidences that show PON1 has beneficial effect against atherosclerosis by protection of HDL-C from peroxidation and plasma membrane from injury thereof. In clinical studies on patients with type 1 diabetes have demonstrated the reduced level of PON1 activity compared to healthy group (15). Different studies have shown that antioxidant therapy is one of the most important treatment strategies for diabetic patients (18).…”
Section: Effect Of Alpha Lipoic Acid On Serum Level Of Pon1 Activity and Correlation Between Pon 1 Activity With Hdl-c And Atherogenic Inmentioning
confidence: 99%
“…A previous study by Patel et al (2014) demonstrated that treatment with N-acetylcysteine amide (NACA), a modified form of NAC, significantly reduced the severity of histopathological damage and improved hindlimb motor function that was associated with normalized glutathione levels following contusion SCI (26). Therefore, the neuroprotective effects of NAC in the present study are likely to be due to the antioxidative and antiinflammatory effects (27).…”
Section: Discussionmentioning
confidence: 49%
“…In the last two years, many research studies, focusing on the identification of drugs potentially effective in SCI treatment, have been published [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Overview Of Current Pharmacological Approaches For the Trmentioning
confidence: 99%